The problem of Terminologization and Conceptualization of Politically Correct Expressions of Sociolinguistics in the KazakhLinguistics (Eurasian Journal of Philology Science and Education, 2015)
The article deals with politically correct expressions widely used in such humanitarian sciences as ethnography, sociolinguistics, culturology and as well as in language policy. The political correctness assumes the change ofwords, having sexual attachment by those having neutral forms, and the use of different forms with «challenged» instead of previously used simple words denoting peoples with physical disabilities as ‘blind’, ‘invalid’, ‘lame’ and many others. Politically correctness is not to be confused with scientific correctness. Sometimes politically correct expressions get into conflict with scientifically correct expressions, while the supporters of politically correctness demand thechange of scientifically correct terms to politically correct ones. Sometimes politically correct terms coincide with scientifically correct ones. The first usage of these expressions in American English was traced, approaches of politically correct phrases terminologisation and explanation in Kazakh linguistics were provided.
Keywords: politically correctness; language policy; sociolinguistics; terminologisation; Kazakh linguistics